2003
DOI: 10.1136/thorax.58.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between levels of nitrogen oxides and peroxynitrite inhibitory activity in chronic obstructive pulmonary disease

Abstract: Background: The prevalent theory concerning the pathogenesis of chronic obstructive pulmonary disease (COPD) is of an imbalance between oxidants and antioxidants in the lung. It has recently been reported that the production of peroxynitrite, an extremely potent oxidant, is increased in the airways of patients with COPD. A study was undertaken of the imbalance between the levels of nitrogen oxides and antioxidant activity against peroxynitrite in the airways of patients with COPD. Methods: Sputum induction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
0
30
0
5
Order By: Relevance
“…The reason why exhaled NO may be elevated in COPD as much as in asthma may be because exhaled NO levels are depressed by cigarette smoking and oxidative stress, since NO combines avidly with superoxide anions to form peroxynitrite. This is supported by the fact that nitrate concentrations, formed by metabolism of peroxynitrite, are increased in breath condensate and sputum of cigarette smokers and patients with COPD (Corradi et al, 2001;Kanazawa et al, 2003c). Generation of superoxide anions from neutrophils also decreases the amount of NO formed by an epithelial cell line in vitro, as NO is consumed to form peroxynitrite .…”
Section: Nitric Oxidementioning
confidence: 91%
See 1 more Smart Citation
“…The reason why exhaled NO may be elevated in COPD as much as in asthma may be because exhaled NO levels are depressed by cigarette smoking and oxidative stress, since NO combines avidly with superoxide anions to form peroxynitrite. This is supported by the fact that nitrate concentrations, formed by metabolism of peroxynitrite, are increased in breath condensate and sputum of cigarette smokers and patients with COPD (Corradi et al, 2001;Kanazawa et al, 2003c). Generation of superoxide anions from neutrophils also decreases the amount of NO formed by an epithelial cell line in vitro, as NO is consumed to form peroxynitrite .…”
Section: Nitric Oxidementioning
confidence: 91%
“…Generation of superoxide anions from neutrophils also decreases the amount of NO formed by an epithelial cell line in vitro, as NO is consumed to form peroxynitrite . There is also a reduction in the undefined "peroxynitrite inhibitory activity" in sputum of COPD patients (Kanazawa et al, 2003c). Peroxynitrite reacts with tyrosine residues in certain proteins to form 3-nitrotyrosine, which may be detected immunologically.…”
Section: Nitric Oxidementioning
confidence: 99%
“…A recent study by KANAZAWA et al [40] has shown that increased levels of NO and reduced peroxynitrite inhibitory activity were present in induced sputum from patients with COPD. The increased level of RNS was inhibited following steroid therapy in patients with COPD, and the reduction in nitrotyrosine and iNOS immunoreactivity in sputum cells was correlated with the improvement in FEV1 and airway responsiveness to histamine [41].…”
Section: Oxidative Stress In Bloodmentioning
confidence: 99%
“…Nitroxidative stress is indeed increased in COPD, and inhibition of inducible nitric oxide synthase protects mice from smoke-induced emphysema and pulmonary hypertension [87][88][89][90]. When folic acid is administered in supraphysiologic doses, high intracellular concentrations of tetrahydrofolates accumulate in most cells, and can exert potent oxidant scavenging effects most notably, scavenging of peroxynitrite -derived radicals [91,92].…”
Section: Adjuvant Strategies Targeting Nrf2mentioning
confidence: 99%